Application of PDEODE Learning Model to Increase Student's KPS in Buffer Solution - Halimah, Mamah; Langitasari, Indah; Solfarina, Solfarina (widiyanto, 2019)
Penelitian ini bertujuan untuk mengetahui peningkatan KPS siswa melalui penerapan model pembelajaran PDEODE. Desain penelitian ini adalah one group pretest-posttest dengan teknik pengambilan sampel purposive sampling. Intrumen pengukuran yang digunakan berupa tes pilihan ganda berjumlah 30 soal dan lembar observasi yang telah tervalidasi. Teknik analisis data yang digunakan adalah analisis deskriptif menggunakan N-Gain dan analisis statistik menggunakan uji t dependen. Berdasarkan hasil penelitian diketahui bahwa adanya peningkatan KPS siswa akibat penerapan model pembelajaran PDEODE. Peningkatan ini dibuktikan oleh hasil uji t yang memiliki nilai signifikansi sebesar 0,000. Nilai N-Gain yang diperoleh pada masing masing indikator yang diteliti adalah indikator menafsirkan (0,682), indikator mengelompokkan (0,338), indikator mengamati (0,569), meramalkan (0,456), mengajukan pertanyaan (0,506), merumuskan hipotesis (0,433), merancang percobaan (0,511), menggunakan alat/bahan (0,449), menerapkan konsep (0,458) dan berkomunikasi (0,529). Dapat dibuktikan bahwa KPS siswa meningkatThis study aims to determine the increasing of students' KPS through the application of the PDEODE learning model. The design of this study was one group pretest-posttest with purposive sampling technique. The measurement instruments that be used were multiple choice tests with a total of 30 questions and validated observation sheets. Data analysis techniques that used in the form of descriptive analysis using N-Gain and statistical analysis using the dependent t test. Based on the results of the research, it was found that there was a development in student KPSPSS due to the application of the PDEODE learning model. This development was proved by the results of the t test which has a significant value of 0,000. N-Gain values that obtained in each indicator that be observed were interpreting indicators (0.682), grouping indicators (0.338), observing indicators (0.569), predicting (0.456), asking questions (0.506), formulating hypotheses (0.433), designing experiments (0.511), using tools/materials (0.449), applying the concept (0.458) and communicating (0.529). It can be proven that student KPS is increasing